A Surface‐Functionalized Ionovoltaic Device for Probing Ion‐Specific Adsorption at the Solid–Liquid Interface. Issue 3 (28th November 2018) - Yoon, Sun Geun; Yang, YoungJun; Jin, Huding; Lee, Won Hyung; Sohn, Ahrum; Kim, Sang‐Woo; Park, Junwoo; Kim, Youn Sang
Abstract: Aqueous ion–solid interfacial interactions at an electric double layer (EDL) are studied in various research fields. However, details of the interactions at the EDL are still not fully understood due to complexity induced from the specific conditions of the solid and liquid parts. Several technical tools for ion–solid interfacial probing are experimentally and practically proposed, but they still show limitations in applicability due to the complicated measurements. Recently, an energy conversion device based on ion dynamics (called ionovoltaic device) was also introduced as another monitoring tool for the EDL, showing applicability as a novel probing method for interfacial interactions. Herein, a monitoring technique for specific ion adsorption (Cu 2+ and Pb 2+ in the range of 5 × 10 −6 –1000 × 10 −6 m ) in the solid–liquid interface based on the ionovoltaic device is newly demonstrated. The specific ion adsorption and the corresponding interfacial potentials profiles are also investigated to elucidate a working mechanism of the device. The results give the insight of molecular‐level ion adsorption through macroscopic water‐motion‐induced electricity generation. The simple and cost‐effective detection of the device provides an innovative route for monitoring specific adsorption and expandability as a monitoring tool for various solid–liquid interfacial phenomena that are unrevealed. Abstract : Ion‐specific‐adsorption‐induced electric potential variations in a water energy‐conversion device are proposed for probing solid–liquid interfacial adsorption phenomena and selective detection of heavy‐metal ions (Cu 2+ and Pb 2+ ). Ion–ligand interfacial interactions are correlated with selective electric potential variations in the device, and the corresponding potential profiles in the interface are proposed as a working mechanism.